3‐Bromo‐2‐Pyrone: An Alternative and Convenient Route to Functionalized Phosphinines. Issue 36 (2nd August 2016) - Habicht, Marija H.; Wossidlo, Friedrich; Weber, Manuela; Müller, Christian
Abstract: The facile access to 3‐bromo‐2‐pyrone allows the preparation of 6‐bromo‐2‐trimethylsilyl‐phosphinine by a [4+2] cycloaddition with Me3 Si‐C≡P for the first time. The regioselectivity of this reaction could be verified by means of single crystal X‐ray diffraction of the corresponding W 0 complex. In the presence of ZnBr2 and dppp (1, 3‐bis(diphenylphosphino)propane) as a bidentate ligand, the bromo‐phosphinine quantitatively undergoes a Negishi cross‐coupling reaction with PhLi that selectively leads to 6‐phenyl‐2‐trimethylsilyl‐phosphinine. This heterocycle could again be characterized by means of X‐ray diffraction as a W 0 complex. These results describe a new and convenient route to 2, 6‐disubstituted phosphinines that makes use of readily available starting materials. Abstract : New functionalized phosphorus heterocycles : A convenient and straightforward synthetic route to 6‐bromo‐2‐trimethylsilyl‐phosphinine was developed, starting from 3‐bromo‐2‐pyrone and Me3 Si−C≡P. The quantitative [4+2] cycloaddition of the starting materials turned out to be regioselective, which was verified by single crystal X‐ray diffraction. A subsequent Pd‐catalyzed Negishi cross‐coupling reaction allows further access to 2, 6‐disubstiuted aromatic phosphorus heterocycles (see figure).